Reality and language in The Voyage Out, by Virginia Woolf = Realidade e linguagem em The Voyage Out, de Virginia Woolf - Peter James Harris; Maria Alessandra Galbiati (Acta Scientiarum: Language and Culture, 2010)
This article discusses one of Virginia Woolf’s greatest literary concerns: the difficulty of expressing human experience through language. The focus is on The Voyage Out, her first novel, published in 1915, particularly the conflicts and contrasts present not only in the trajectory of Rachel Vinrace, the main character, but also in the structure of the novel itself, which establish a constant tension between reality and language. Este artigo tem como objetivo discutir uma das maiores preocupações literárias de Virginia Woolf: a dificuldade de expressar a experiência humana por meio da linguagem. Focalizamos The Voyage Out, seu primeiro romance, publicado em 1915, com atenção especial para osconflitos e contrastes presentes tanto na trajetória de Rachel Vinrace, a personagem principal, como na própria estruturação do romance, que instauram a tensão constante entre realidade e linguagem.